1999
DOI: 10.1034/j.1399-6576.1999.430714.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐injection paravertebral block compared to general anaesthesia in breast surgery

Abstract: Single-injection paravertebral block at the level of T4 represents a suitable alternative to general anaesthesia in women undergoing breast surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
112
1
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 193 publications
(125 citation statements)
references
References 0 publications
4
112
1
7
Order By: Relevance
“…15 As might be expected, previous small studies generally overestimated treatment effect, with some reporting differences exceeding three points on an 11-point scale. 24 Combining all studies, the overall pain benefit was a reduction by more than 2, an amount which was highly statistically significant but probably also reflects a clinically important reduction in discomfort.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…15 As might be expected, previous small studies generally overestimated treatment effect, with some reporting differences exceeding three points on an 11-point scale. 24 Combining all studies, the overall pain benefit was a reduction by more than 2, an amount which was highly statistically significant but probably also reflects a clinically important reduction in discomfort.…”
Section: Discussionmentioning
confidence: 93%
“…4 and 5. For worst pain score in the immediate two postoperative hours, the recent relevant meta-analysis 23 contained five eligible trials [24][25][26][27][28] evaluating paravertebral anesthesia as a single technique vs GA and five eligible trials 14,15,[29][30][31] evaluating the combination of paravertebral analgesia and GA vs GA alone. One additional recent trial 32 was identified and included in our meta-analysis along with our current results.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations